PATENTING FOR THE FOREST COMPLEX: DIRECTIONS OF DEVELOPMENT OF THE NORTHERN (ARCTIC) FEDERAL UNIVERSITY NAMED AFTER MV LOMONOSOVA (NArFU) - Shegelman I. R., Vasilyev A. S., Budnik P. V. (Modern education development: theory, techniques and practice, 2019)
The analysis of patentable intellectual property objects of the Northern (Arctic) Federal University named after M.V. Lomonosov (NArFU) in the forest complex. The main directions of development of patented by the University of intellectual property for the forest complex.
Keywords: интеллектуальная собственность; лесной комплекс; патент; результаты интеллектуальной деятельности; Северный (Арктический) федеральный университет; intellectual property; forestry; patent; Northern (Arctic) Federal University